PERHITUNGAN KEMBALI PAJAK PENGHASILAN BADAN SESUAI DENGAN PERATURAN PEMERINTAH NOMOR 23 TAHUN 2018 UNTUK MENENTUKAN PAJAK TERUTANG - Siti Tsnaniati; Dhiki Dwi, Anggoro; Nanang, Rohadi; Nurul, Hidayah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2020)
Corporate Income Tax is a tax that is levied on income received or obtained by the Agency asreferred to in the General Provisions Act and Tax Procedures, including taxpayers,withholders and tax collectors. The tax payable is a tax that must be paid at any time, in thetax period, in the tax year, or in part of the year in accordance with the Tax Regulations.Through the recalculation of Corporate Income Tax in accordance with GovernmentRegulation Number 23 of 2018 to determine the Debt Tax. The purpose of this study is todetermine the recalculation of corporate income tax in accordance with GovernmentRegulation No. 23 of 2018 in order to determine the tax payable. The data source used in thisstudy is primary data. The type of data used is qualitative and quantitative data. The variablesused are corporate income tax and tax payable. This research uses descriptive quantitativeresearch.Based on the analysis, the Calculation of Corporate Income Tax based onGovernment Regulation Number 23 of 2018 uses the Base Tax Imposition sourced from Salesto Members and Service Revenues at a lower rate of 0.5%, so from the recalculation of IncomeTaxes it was found that the amount of Tax Payable which is calculated based on GovernmentRegulation Number 23 of 2018 is lower than that calculated based on Government RegulationNumber 46 of 2013. Based on the results of the study, the researchers suggest that KPRI ManisKras should calculate the Corporate Income Tax in accordance with Government RegulationNumber 23 of 2018 in fulfilling the Obligatory Tax obligations that must be paid by KPRIManis.